Testing the WHO responsiveness concept in the Iranian mental healthcare system: a qualitative study of service users - Forouzan Ameneh; Ghazinour Mehdi; Dejman Masoumeh; Rafeiey Hassan; Sebastian Miguel (BMC, 2011)
Abstract Background Individuals' experience of interacting with the healthcare system has significant impact on their overall health and well-being. To relate patients' experiences to a common set of standards, the World Health Organization (WHO) developed the concept of health system responsiveness. This study aimed to assess if the WHO responsiveness concept reflected the non-medical expectations of mental healthcare users in Teheran. Methods In this qualitative study, four mixed focus group discussions were formed, comprising 53 mental health service users in Tehran, Iran, in 2010. Content analysis was performed for data analysis. Responses were examined in relation to the eight domains of the WHO's responsiveness model. Results There were many commonalities between the findings of this study and the eight domains of the WHO responsiveness model, although some variations were found. Effective care was a new domain generated from our findings. In addition, the domain of prompt attention was included in two new labelled domains: attention and access to care. Participants could not differentiate autonomy from choice of healthcare provider, believing that free choice is part of autonomy. Therefore these domains were unified under the name of autonomy. The domains of quality of basic amenities, access to social support, dignity and confidentiality were considered to be important for the responsiveness concept. Some differences regarding how these domains should be defined were observed, however. Conclusions The results showed that the concept of responsiveness developed by the WHO is applicable to mental health services in Iran. These findings might help policy-makers' better understanding of what is useful for the improvement of mental health services.